The MAMOVI Method for Training the Heimlich Maneuver in Adolescents - Girianto, Pria Wahyu Romadhon; Damayanti, Didit; Pebrianti, Anisa Ajeng (Chakra Brahmanda Lentera Institute, 2023)
Background: Choking is a condition of total or partial obstruction of the airway that requires immediate action to avoid death or disability. The lack of information means that PMR members have not been able to implement choke management appropriately. This study aimed to see how Heimlich maneuver training using the MAMOVI method (lectures, demonstrations, and videos) affected PMR members at SMPN 1 Ngantang's ability to provide choking first aid Methods: Pre Pre-experimental design research design with a one-group pretest-posttest approach without control. The sampling technique with Purposive Sampling obtained 21 respondents from 70 populations. The research instrument used a choking first aid ability observation sheet, with a Wilcoxon Signed Rank Test statistical test with a significance level of 0.05 Results: The result of the study before being given the Heimlich Maneuver training intervention showed that (100%) respondents had less ability. After receiving complete (100%) intervention, respondents demonstrated excellent skills. The mean pre-test score was 3.71, and the mean post-test score was 26.71. It showed an increase in the value before and after the intervention was given. The analysis yielded a sig (2-tailed) p-value of 0.000 ≤.05, so that the p-value comparable000 toiindicating that Heimlich Maneuver training with the MAMOVI method (lectures, demonstrations, videos) has an effect on PMR members at SMPN 1 Ngantang's ability to perform choking first aid. Conclusion: The MAMOVI method combined the three methods to make it more interactive, interesting, effective, and understandable for respondents. We recommend that all school residents socialize this ability to prevent choking events